Correlates of contraceptive use and breastfeeding practice - Feranil, Alan Banzon 1953- (1982)
Using data on currently married couples in Pangasinan and Southern Leyte derived from the 1976 Mortality Fertility and Family Formulation Survey, the correlates and determinants of contraceptives and breastfeeding practice were examined. The significant background variables (i.e. Socio-economic and demographic characteristics) and fertility perceptions were ascertained using stepwise multiple regression analysis.
Generally, more background variables proved to be relatively more correlated with breastfeeding and contraceptive practice than fertility perceptions and intentions. In addition, the significance of variables were shown to be exclusively important for a particular province or for a particular sex of respondents. Among the variables, education figured prominently as the most significant determinant for contraceptive use
(for both husband and wives) and breastfeeding practice.
Disparities between husbands’ and wives’ contraceptive use revealed the greater concern wives have towards family size limitation than their husbands. Moreover, correlates which were shown to be exclusively significant for husbands or wives indicate that factors which may affect a couple’s behavior could have diverse effects on either spouse.
The difference between a developed and a less developed area was not
illustrated in the study. Contraceptive and breastfeeding practice were found to be relatively traditional in Pangasinan than Southern Leyte, typical of a developed area it was supposed to represent.
The relatively low explanatory power offered by the few significant variables correlated with the selected intermediate variables reveal the multi-faceted nature of behavioral patterns, and the need to incorporate other factors in studying contraceptive and breastfeeding practice in the future.
Vita.
Thesis
Keywords: Contraception -- Philippines -- Pangasinan; Breast feeding -- Philippines -- Pangasinan; Breast feeding -- Philippines -- Southern Leyte; Contraception -- Philippines -- Southern Leyte